Mitos Kelas Menengah ke Atas dalam Desain Iklan Politik Risma-Bambang - Bahruddin, Muh. (Institute of Research and Community Outreach - Petra Christian University, 2012)
Local elections (pilkada) in the entire territory of Indonesia affect the huge presence of the candidate's political advertising. This study examines myths about the middle to upper class in political advertising design of Risma-Bambang who won the mayoral election of Surabaya in 2010. This advertising design is interesting to study because it has a different concept of political advertising in general (out of the mainstream). The other candidate's political advertising design accentuate the face image in attracting potential voters in contras to political advertising design of Risma- Bambang that shous just a lot of display symbols that are accompanied with the tagline